Seeking Meaning Behind Epistolary Clichés: Intercessory Prayer Clauses in Christian Letters. (4th January 2016) - Choy, Renie
Abstract : The letter, as the format of twenty-one of the twenty-seven documents in the canonical New Testament, is arguably the literary form which has played the most significant role in the history of Christianity. But scholars have often been troubled by how to treat the conventions framing Christian letters: since little of Christian literature from its earliest time to the medieval period escapes the influence of classical traditions of rhetoric, can constant epistolary formulas be taken as expressions of genuine sentiment? In fact, it is precisely because the lines between classical influence and Christian innovation are so difficult to make out that E. R. Curtius was able to argue that the humility formula of medieval charters, for so long assumed to have originated in Paul, was in fact a pagan Hellenistic prototype like scores of other rhetorical conventions. His study of the formula serves, Curtius writes, to 'furnish a warning against making the Middle Ages more Christian or more pious than it was', and to demonstrate that 'a constant literary formula must not be regarded as the expression of spontaneous sentiment'. So the entrenchment of rhetoric in letter-writing is often set in opposition to genuine Christian feeling, commonplace utterance against living expression, empty verbiage against religious sincerity.